2021
DOI: 10.3390/rs13224582
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Applicability and Scaling Effects of Satellite-Observed Spring and Autumn Phenology in Complex Terrain Regions Using Four Different Spatial Resolution Products

Abstract: The information on land surface phenology (LSP) was extracted from remote sensing data in many studies. However, few studies have evaluated the impacts of satellite products with different spatial resolutions on LSP extraction over regions with a heterogeneous topography. To bridge this knowledge gap, this study took the Loess Plateau as an example region and employed four types of satellite data with different spatial resolutions (250, 500, and 1000 m MODIS NDVI during the period 2001–2020 and ~10 km GIMMS3g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 76 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…The upper limit of the reasonable observation scale was 70 m for the remote sensing interpretation of the alpine pine forests of the plot in Shangri La City, and the optimal spatial scale was 50 m for biomass estimation (Wang et al, 2020). It was found that the phenology that was derived from the data with a 1,000 m spatial resolution in the heterogeneous topography regions was feasible in Loess Plateau with its numerous gullies (Chen et al, 2021). The scale effect showed the most obvious difference between the element types and the index types, while it became smaller in the range of 21–90 km and disappeared beyond 90 km.…”
Section: Discussionmentioning
confidence: 99%
“…The upper limit of the reasonable observation scale was 70 m for the remote sensing interpretation of the alpine pine forests of the plot in Shangri La City, and the optimal spatial scale was 50 m for biomass estimation (Wang et al, 2020). It was found that the phenology that was derived from the data with a 1,000 m spatial resolution in the heterogeneous topography regions was feasible in Loess Plateau with its numerous gullies (Chen et al, 2021). The scale effect showed the most obvious difference between the element types and the index types, while it became smaller in the range of 21–90 km and disappeared beyond 90 km.…”
Section: Discussionmentioning
confidence: 99%
“…The only highly significant correlation (r = -0.52519) found in our study was between elevation and the probability of meadow decline to the 30th percentile of the land during severe drought, with a smaller effect of slope and slope orientation on meadow drought ( Figure 15 ). This is because the NDVI representing grasslands in our study used lower resolution (1/12°) GIMMS data that do not capture the effects of slope and slope orientation on grassland drought ( Chen et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Spring events in Louros and the other phenophases of P. fruticosa showed weak or no trends for change. The advancement of spring phenology is one of the consistent observations across Northern Europe [ 18 ], North America [ 30 ], and China [ 5 ] during the two recent decades. In Mediterranean-type ecosystems, the spring phenology trends show scattered spatial pattern according to a comprehensive study of Ivits et al [ 4 ]; over the southern Mediterranean region, an earlier start-of-season was observed, whereas over parts of the northern Mediterranean basin a growing season shift towards later dates was evident.…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding of vegetation function, its interactions with the climate, the key controlling mechanisms, and its vulnerability to climate change are far from complete. Evidently, understanding climatic influences on processes and interactions enables the prediction of changes under different climatic scenarios [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%